LEGAL STABILITY AND SOCIAL CHANGE: NOTES ON THE COLLECTIVE CRIMINAL PROCEDURE OF THE CONTEMPORARY RISK SOCIETY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Contemporary society is marked by a series of transformation processes that break with the way we represent legal guardianship. In criminal and criminal procedural matters, this process is directly linked to diffuse and collective legal assets. The existence of these assets has become an object of great debate in criminal matters, however in criminal procedural law the doctrine is very timid in seeking a path towards the Collective Criminal Procedure. The present work deals with this we point out that will be done on the need to establish the bases of a Collective Criminal Procedural Law.